Comparative Effectiveness of Animated Video Versus Storytelling Distraction on Procedural Pain in Preschool Children During Intravenous Insertion - Yunita Anggrain; Herry Susanto; Indra Tri Astuti; Siriluk Winitchayothin (LPPM Universitas Harapan Bangsa, 2026)
Intravenous (IV) insertion is a common invasive procedure in preschool children and frequently causes pain and distress because of limited developmental ability to understand and cope with the procedure. Effective non-pharmacological strategies are essential to reduce procedural pain and support atraumatic pediatric care. This study aimed to compare the effectiveness of animated video distraction and storytelling in reducing pain during IV insertion among children aged 3-5 years. A quasi-experimental posttest-only design was conducted in the emergency department of a tertiary hospital. Thirty-two preschool children were recruited using purposive sampling and non-randomly allocated to an animated video group (n = 16) or a storytelling group (n = 16). Pain intensity during IV insertion was assessed using the Face, Legs, Activity, Cry, and Consolability (FLACC) scale. Data were analyzed using descriptive statistics, the Shapiro-Wilk test, and the Mann-Whitney U test. Most children in both groups experienced moderate pain following intervention. The animated video group demonstrated a lower mean FLACC score (3.94) compared to the storytelling group (4.75). Statistical analysis revealed a significant difference in pain levels between the two interventions (Z = -2.015; p = 0.044; effect size r = 0.36), indicating greater effectiveness of animated video distraction. Both distraction methods reduced procedural pain, although animated video distraction was associated with significantly lower pain than storytelling in this single-site emergency department sample. These findings support the integration of audiovisual distraction into pediatric nursing practice to improve comfort and cooperation during IV insertion while future randomized studies are recommended to confirm these results.